Autonomy-supportive pedagogical approach to sports coaching: research, challenges and opportunities - Occhino, J. L.; Mallett, C. J.; Rynne, S. B.; Carlisle, K. N. (International Journal of Sports Science and Coaching, 2014)
There has been an increasing body of research on autonomy- or need-support specific to a coaching context that warrants some review of what we know and don't know, and what might be generative for future research. The previous studies reviewed within this article have shown consistent support for Self-determination theory with autonomy-supportive environments linked with adaptive outcomes, such as superior performance, enhanced self-worth, increased effort, and self-determined motivation; while controlling environments have been linked with increased attrition and extrinsic motivation or amotivation. In this way, much of the research in autonomy-supportive coaching has focused on the impact of coaching behaviours on athlete outcomes. While this is an important focus of inquiry, there has been a dearth of research examining those causal factors that impact coaches' pedagogical behaviours in the first case. This review underscores the need for future research to examine the antecedents to coaching behaviours, which is central to understanding the complexity and challenges in promoting an autonomy-supportive approach to sport coaching.